Makna Pencobaan Menurut Yakobus 1:12-15 Dan Implikasinya Bagi Pelayan Tuhan Masa Kini - Aben Tuke Banamtuan; Abad Jaya Zega (Publisher STPKat, 2023)
James 1:12-15 is a Bible verse that delves into the meaning of trials and their impact on modern-day servants of God. The verse underscores that trials are a part of life, testing one's faith and character. In this context, the meaning of trials is the tests or challenges faced by every individual, including servants of God, and its implications are significant for their outlook and behavior. The verse teaches that those who endure through trials will receive blessings in the form of the